The evolution of financial services in the Caribbean and its implications for macroeconomic stability - Da Costa, Michael ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Highlights some of the key recent trends in the activities of banks and other financial institutions in the Caribbean region. Discusses some broad, preliminary observations regarding the implications of some of these activities for macroeconomic management and financial sesctor regulation and stability.